PENGARUH PARTISIPASI PENYUSUNAN RENCANA BISNIS ANGGARAN (RBA), KOMITMEN ORGANISASI, DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA UNIVERSITAS BENGKULU - Sari, Kartika Mayang; Abdullah, Abdullah (Jurnal Akuntansi, 2019)
The research was aimed to examine and obtain empirical evidences of the influence of budget participation bussiness plan, commitment of organization, and motivation of work to performance official at the University of Bengkulu. This research used a purposive sampling. The sample was used in the research was 65 respondents of official at the University of Bengkulu. The data in this study was the primary data that has obtained from the directly spread questioner to the respondens. The questionnaire distributed to 59 which can be analyzed. The multiple linear regression analysis was used to analyze the hypothesis with SPSS 16 program. The result of this study explained that budget participation bussiness plan, commitment of organization, and motivation of work were positive affected to performance official at the University of Bengkulu.